Cellular and molecular aspects of immunologic compatibility of implants with nanostructured calcium phosphate coating - I. A. Khlusov; M. A. Surmeneva; R. A. Surmenev; N. V. Ryazantseva; O. Ye. Savelieva .; A. A. Ivanova; T. S. Prokhorenko; L. A. Tashireva; M. V. Dvornichenko; V. F. Pichugin (Бюллетень сибирской медицины)
Jurkat tat cell line reaction on short-term (24 h) in vitro contact with model composite implants designed for bone tissue bioengineering has been studied. The titanium samples was coated by thin nanostructured calcium phosphate (CaP) layer was formed by rf-magnetron sputtered deposition. An increase in the number of leukemic line T-lymphoblasts presented CD124, CD25, CD4, CD8, CD16/56 markers of cell maturation and differentiation has been revealed with the help of Wilcoxon T-test. In a case of CD8 positive cells the differences reached to statistic levels (Mann—Whitney U-test) as compared with cells had no contact with model implants. No implants effect was mediated by cytokines secretion (IL-1b, IL-2, IL-4, IL-6, IL-8, IL-10 and TNFα). An elevation of apoptotic and necrotic cells number has been not revealed. Silicone incorporation into CaP composition had no essential modulating action on indices studied. A conclusion about an absence of immunotoxic effect of investigated coatings as regards to T-cell immunity has been made. In vitro acceleration of CD8 presentation by human T-lymphoblasts may be conditioned by their direct interaction with artificial CaP surfaces.